Selective Reduction of a Heterotopic Cesarean Scar Pregnancy Complicated by Septic Abortion - Tymon-Rosario, Joan (Case Rep Obstet Gynecol, 2018)
BACKGROUND: Heterotopic pregnancy involving the implantation of an ectopic pregnancy into a prior cesarean scar with a concurrent intrauterine pregnancy is a rare and potentially life-threatening condition with minimal information in the literature to guide treatment and management options. CASE: A 40-year-old G5P3103 at 12 weeks and 3 days with a history of two cesarean deliveries was diagnosed with a live heterotopic pregnancy containing a cesarean scar ectopic and an intrauterine pregnancy. After selective reduction of the cesarean scar gestation with potassium chloride (KCl), the patient presented ten days later to the emergency department with septic abortion and sepsis. The patient underwent bilateral uterine artery embolization followed by ultrasound guided uterine evacuation with dilation and curettage, which was complicated by intraoperative hemorrhage and persistent bacteremia. The patient had resolution of her bacteremia after total abdominal hysterectomy. CONCLUSION: Conservative management of uterine infection resulting from selective reduction of a heterotopic pregnancy cesarean scar pregnancy may be considered; however, severe septicemia and persistent bacteremia may necessitate definitive surgical management.